2015
DOI: 10.1371/journal.pone.0139002
|View full text |Cite
|
Sign up to set email alerts
|

Differential microRNA Analysis of Glandular Trichomes and Young Leaves in Xanthium strumarium L. Reveals Their Putative Roles in Regulating Terpenoid Biosynthesis

Abstract: The medicinal plant Xanthium strumarium L. (X. strumarium) is covered with glandular trichomes, which are the sites for synthesizing pharmacologically active terpenoids such as xanthatin. MicroRNAs (miRNAs) are a class of 21–24 nucleotide (nt) non-coding RNAs, most of which are identified as regulators of plant growth development. Identification of miRNAs involved in the biosynthesis of plant secondary metabolites remains limited. In this study, high-throughput Illumina sequencing, combined with target gene pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…Various microRNAs have been identified to be associated with secondary metabolism (Wu et al, 2012; Lu S. et al, 2013; Fan et al, 2015; Wei et al, 2015). However, the regulatory roles of non-coding RNAs in PQ and UQ biosynthesis have not been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Various microRNAs have been identified to be associated with secondary metabolism (Wu et al, 2012; Lu S. et al, 2013; Fan et al, 2015; Wei et al, 2015). However, the regulatory roles of non-coding RNAs in PQ and UQ biosynthesis have not been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Using NGS technology, several miRNAs involved in the sesquiterpene biosynthesis pathway have been mapped and validated in X. strumarium . For example, mRNAs of the upstream enzymes in the pathways of terpenoid biosynthesis, including 1-deoxy-D-xylulose 5-phosphate synthase (DXS), 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR), isopentenyl diphosphate (IPP)/dimethylallyl diphosphate (DMAPP) synthase (IDS), and isopenteyl diphosphate isomerase (IDI) were predicted to be targeted by miR7539, miR5021, and miR1134 (Fan et al, 2015). The complete list of miRNAs and their target genes have been provided in Table 1.…”
Section: Role Of Mirnas In Terpenoid Biosynthesismentioning
confidence: 99%
“…In earlier reports, the regulation of miR5021 was frequently observed for the terpenoid biosynthesis. In the case of mevalonate pathway, the regulation of HMGR was reported by miR5021 in Xanthium strumarium (Fan et al, 2015). Isopentenyl diphosphate (IPP) works as a precursor molecule for terpenoid derivatives.…”
Section: Functional Annotation and Pathway Analysismentioning
confidence: 99%
“…Isopentenyl diphosphate (IPP) works as a precursor molecule for terpenoid derivatives. Isopentenyl diphosphate synthase (IDS) and isopenteyl diphosphate isomerase (IDI) are key enzymes reported for involvement in the formation of IPP, and being regulated by miR5021 (Fan et al, 2015). Our study revealed that the miR5021 may control the essential oil biosynthesis by controlling gene expression of enzymes involved in 2-C-methyl-D-erythritol 4-phosphate (MEP)/1-deoxy-D-xylulose 5-phosphate pathway (DOXP) including geranyl di-phosphate synthase (EC: 2.5.1.29) ( Table 2 and Supplementary 3).…”
Section: Functional Annotation and Pathway Analysismentioning
confidence: 99%